Dejavniki otrokove pripravljenosti za šolo - Marjanovič Umek, Ljubica (Psihološka obzorja (Ljubljana), 2006)
The purpose of the study was to examine the effect of preschool on children's school readiness in connection with their intellectual abilities, language competence, and parents' education. The sample included 219 children who were 68 to 83 months old and were attending the first year of primary school. Children were differentiated by whether or not they had attanded preschool before starting school. Children's intelectual ability was determined using Raven's coloured progressive matrices (CPM; Raven, Raven & Court, 1999), language competence using the Lestvice splošnega govornega razvoja - LJ (LSGR-LJ, Scales of general language development; Marjanovič Umek, Kranjc, Fekonja in Bajc, 2004), and school readiness with the Preizkus pripravljenosti za šolo (PPŠ, Test of school readiness; Toličič, 1986). The results indicate that children's intelectual ability and language competence have a high predicitve value for the school readiness - they explained 51% of the variance in children's scores on the PPŠ. Preschool enrolment has a positive effect on school readiness for children whose parents have a low level of education, but not for those whose parents are highly educated.
Keywords: otroci; child; school; šola; pripravljenost za šolo; intelektualne sposobnosti; izobrazba staršev; psihologija; psychology